The effect of the paksa method on primary students' achievement of the subject - Abdullah Ismail, Muna (International Journal of Psychosocial Rehabilitation, 2020)
The aim of research is to identify the impact of the paksa method on primary school students' achievement of the academic subject and also to verify the research goal; the following zero hypothesis was formulated. There is no statistically significant difference at the level of significance (0.05) between the average levels of achievement of students (the experimental group) who study according to the method (paksa) in science and the average levels of students ’achievement (control group) in the subject of science who study according to the method. Regular (discussion and questioning) experimental design with experimental and control groups and post-test subjects was chosen.The research community was represented by the fifth primary class students (Al-Dhad Elementary School for Boys), whose number (70) was distributed as two groups (A and B) by the experimental group (35) and the control group (35), and by random appointment, groups (A) and (B) were selected. As the research sample, the groups were rewarded in the variables (intelligence and achievement of the previous) in the academic year (2018-2019).The experiment was applied in the first semester of the academic year (2019-2020). The researcher taught two research groups on his own according to the necessary teaching plans: the Baxa method for the experimental group and the usual method for the control group.The results of research showed that using the Z-test for two independent samples of equal number are stated according to the experimental group students who studied according to the (paksa) method were superior to the control group students who studied according to the usual method, as the calculated (Z) reached (2.32), while the (Z) tabular reached (1.96)and from these results he concluded The researcher stated that teaching according to the Baxa method had an effect on students’ achievement, as the effect size reached 0.04 with a small estimate compared to the standard (0.01). Accordingly, the researcher made a number of recommendations, including the adoption of the Baxa method in the subject of science and teacher training during service.